The concept of on-farm adaptive research in the development of livestock production in Nigeria - Little, D.A. (Livestock Planning, Monitoring, Evaluation and Coordination Unit, 1992)
The disparity between the growth rate of the human population and that of food production is such that improvement in livestock productivity is becoming of ever-increasing priority. In the context of sub-Saharan Africa, it is well recognized that approaches to addressing these needs based on the transfer of established technologies from the industrialized world have been singularly unsuccessful. Many reasons have been advanced for this, which might be distilled into an overriding principle that the bases upon which the transferred technologies were developed were inappropriate for the systems to which transfer was attempted. For example, technologies developed largely in temperate areas for specific milk or beef production systems, dependent as they are on large quantities of high quality feed stuffs and many other high cost inputs, are not appropriate for the usually multi-purpose cattle production systems, typical of small-holder farming communities in the developing, largely tropical world. The failure of simple transfer of technology to produce viable solutions has placed increasing emphasis on the need for relevant research at the farmer level. The basic principles of as nutrition and disease control remain valid, but means have to be found by which these can be applied, in particular farming situations, to optimize animal productivity.